2018
DOI: 10.1186/s40748-017-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transcutaneous bilirubinometer (DRAEGER JM 103) use in Zimbabwean newborn babies

Abstract: BackgroundAcute Bilirubin Encephalopathy in the neonatal period is a major cause of permanent disability. Effective screening and surveillance are essential in the newborn period to enable timely management. Noninvasive transcutaneous bilirubin devices have been successfully used for screening in many settings. We evaluated the accuracy of the Draeger JM 103 (Medical Systems, USA) for estimating serum bilirubin in Zimbabwean newborns.MethodsPaired transcutaneous (forehead and sternum) and serum bilirubin measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
3
19
2
4
Order By: Relevance
“…The correlation coefficient between AJO-Neo and TSB measurements of 0.79 that we found in our study is better than those found in Ref. [56][57][58][59][60][61][62][63][64][65] but lesser than Ref. 1,39,61,[66][67][68] .…”
Section: Resultscontrasting
confidence: 81%
“…The correlation coefficient between AJO-Neo and TSB measurements of 0.79 that we found in our study is better than those found in Ref. [56][57][58][59][60][61][62][63][64][65] but lesser than Ref. 1,39,61,[66][67][68] .…”
Section: Resultscontrasting
confidence: 81%
“…The assortment was based on signs and symptoms as described by previous studies. 5 , 6 Convenience sampling and the sample size was calculated using the formula.…”
Section: Methodsmentioning
confidence: 99%
“…1-2 ml of blood was collected with aseptic precaution before administration of starting any antibiotic therapy and carefully transferred into a culture bottle containing Brain Heart Infusion(BHI) Broth immediately to assure the ratio (1:10). 6 …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, abnormal metabolism of BR, especially in newborns, may cause jaundice [15]. In the past few years, a number of BR detection methods have been developed, including those based on enzymatic assays, fluorescence, capillary electrophoresis, high-performance liquid chromatography, chemiluminescence, and piezoelectricity [16,17]. However, during this progress, most BR sensors are complex, costly to operate, and detect BR in an indirect way, which implies that the search for new materials and methods to improve BR sensor sensitivity, selectivity, and stability is still ongoing.…”
Section: Introduction mentioning
confidence: 99%